1981
DOI: 10.1002/eji.1830110310
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic or immunogenic activity of hapten‐conjugated polysaccharides correlated with cellular localization

Abstract: Dinitrophenylated (DNP) conjugates of Ficoll, hydroxyethyl starch, levan, dextran, type 3 pneumococcal capsular polysaccharide SIII, pectin, alginic and hyaluronic acid at various epitope densities were tested for their capacity to inhibit secondary IgG anti-DNP antibody responses using an in vivo transfer system. Some aminobenzylarsonate conjugates were examined similarly. Conjugates of the acidic polysaccharides were markedly more effective than those of uncharged polysaccharides. Conjugated with high epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
3

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 22 publications
2
20
0
3
Order By: Relevance
“…Two functions have been ascribed to marginal zone cells. In earlier work it was shown that these cells are important in immune responses to thymusindependent (T12) antigens (Humphrey, 1981), a result in agreement with the observation that splenectomized individuals who are depleted of marginal zone cells, respond poorly to thymus independent antigens (Amlot & Hayes, 1985). More recently extensive studies in the rat have led to the suggestion that the marginal zone contains memory B cells Kumararatne & MacLennan, 1981;Zhang et al, 1988).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Two functions have been ascribed to marginal zone cells. In earlier work it was shown that these cells are important in immune responses to thymusindependent (T12) antigens (Humphrey, 1981), a result in agreement with the observation that splenectomized individuals who are depleted of marginal zone cells, respond poorly to thymus independent antigens (Amlot & Hayes, 1985). More recently extensive studies in the rat have led to the suggestion that the marginal zone contains memory B cells Kumararatne & MacLennan, 1981;Zhang et al, 1988).…”
Section: Introductionsupporting
confidence: 58%
“…It is likely that somatic mutation events leading to production of high affinity antibodies take place in this site (MacLennan & Gray, 1986). The third population of B cells is that of the splenic marginal zone which contains a mixture of cells at intermediate stages between small lymphocytes and plasmablasts, as well as macrophages (Humphrey, 1981). These B cells express sIgM but not sIgD and have avid Fc and C3 receptors , Liu, Oldfield & MacLennan, 1988.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, even though the presence of T cells hastened class switching, they did not cause a pronounced fall in antibody titer after peak production had been reached, suggesting the absence of a TD regulatory event and potentially reflecting the presence of persisting antigen. Antigen persistence is a characteristic trait of most if not all TI antigens, probably reflecting their complex nature and resistance to degradation, as well as their tendency to be associated with per- sistent infection (20), which are all characteristics of B. burgdorferi infection (7).…”
Section: Discussionmentioning
confidence: 99%
“…For most T-cell-independent type 2 antigens, the prolonged contact of the antigens with membrane immunoglobulin and persistent B-cell signaling is common in inducing a humoral immune response in the absence of helper T cells. 37,38 Consequently, in addition to the density of PEG, it is rational to speculate that extended circulation time also plays an important role in the induction of the ABC phenomenon. Regarding 5 mol% PEG SLNs, because of the only slightly prolonged circulation time, inefficient contact of the PEGylated SLNs with membrane immunoglobulin stimulated B-cells and resulted in secretion of a small amount of anti-PEG IgM, with only a weaker immune response and insignificant ABC phenomenon.…”
Section: Discussionmentioning
confidence: 99%